Iron deficiency anemia in the elderly (Faculty of Medicine Universitas Indonesia, 2011)
The numbers of older people in the world have been growing rapidly. Anemia is the most common hematologic problem encountered in older adults. However, anemia should not be accepted as an inevitable consequence of aging. Anemia in the elderly signifies an underlying disease. Iron Defi ciency Anemia (IDA) is being one of the most common causes of anemia in older people. IDA in the elderly is often associated with such non specific symptoms. The diagnosis of IDA is typically based on laboratory results. Hence, the utilization of the various laboratory tests plays an important role for the diagnosis of IDA. The presence of IDA in the elderly is usually related with gastrointestinal disorders. Thus, gastrointestinal evaluation should be contemplated in all patients with IDA unless there is a history of clinically important non gastrointestinal blood loss. Older people with IDA should have iron supplementation both to correct anemia and to replenish body iron stores. However, the underlying cause should always be treated to prevent further iron loss. (Med J Indones 2011; 20:71-7) Keywords: anemia, elderly, gastrointestinal, iron deficiency